Multiple intelligences among physical education students of Pangasinan State University - Estrella, Erwin O. (PSU Urdaneta Campus Research Journal, 2015)
Howard Gardner's theory of multiple intelligences opens the door for seeing the dynamicity of an individual. This creates a wider perspective of highlighting strengths over weaknesses; thus, academic community must identify the totality of a student through evaluation on various frames of intelligence. This descriptive study determined the level of multiple intelligences among physical education students of Pangasinan State University. Three-hundred three (303) respondents were randomly selected through fishbowl method provided the data by answering a questionnaire. Findings show that the Physical Education students do have the above average level of multiple intelligences along visual. Likewise, chi-square (X^2 c) correlation test results show that there is no significant relationship between the profile in terms age, sex, civil status, monthly family income and academic status and the level of multiple intelligences. Over-all, it is concluded that PSU students possess dominance in terms of of visual and profile had no bearing on the multiple intelligences. The most identifies proposed measure to improve the multiple intelligences is the design of teaching strategies to accommodate the most dominant as well as the recessive multiple intelligences of the students.